ByzRev 08.2026.016: Naomi Ruth Pitamber, Byzantium and Landscapes of Loss.: The Recreation of Constantinople in the Laskarid and Palaiologan Eras. Cambridge: Cambridge University Press 2026. - Altripp, Michael (The Byzantine Review, 2026)
Naomi Ruth Pitamber, Byzantium and Landscapes of Loss. The Recreation of Constantinople in the Laskarid and Palaiologan Eras. Cambridge: Cambridge University Press 2026. XXIV, 330 S. – ISBN 978-1-009-33179-1